Pengabdian Masyarakat dengan “Sosialisasi Pengaruh Penggunaan Gadget pada Anak” di Posyandu Remaja Kelurahan Banyurip - Ni'matul Ulya; Ana Setyowati; Swasti Artanti (Jurnal ABDIMAS-HIP Pengabdian Kepada Masyarakat, 2023)
The development of advanced technology can increase internet usage in adolescents to spend time every day using social media or the like. Gadgets have an important role in human life, as technological advances are created to make big changes from children to adults. On the other hand, gadgets have a negative or bad impact if their use is not adjusted to the actual benefits or functions. Socialization of the "Effect of Gadget Use" at the Youth Posyandu of Banyurip Village, Pekalongan City on Friday, February 10, 2023 with 20 participants. This community service activity was very effective and gave significant results with the results of the participants' knowledge before the socialization was mostly in the moderate category, namely 8 people and after socialization the participants had good knowledge as many as 13 people. The author hopes that teenagers, especially in the Banyurip Village area, can have a positive attitude and can manage their time in using gadgets